An Exploration on Critical Reading Skills of M.A. English Majors at Thu Dau Mot University - Nguyen, Thanh Thai; Du, Thanh Tran (J-SHMIC : Journal of English for Academic, 2024)
Studying at postgraduate level always requires learners to do a large amount of reading for some certain academic purposes. This becomes more notable when reading must be done in a strictly limited amount of time. On this account, postgraduate students must come up with particular strategies for reading. Thus, from the critical thinking perspective, the current study was conducted to investigate the M.A. English majors’ use of reading strategies, especially critical reading skills. Through questionnaire and interview, data for analysis were collected from 30 M.A. students of English and five lecturers of English, who already completed their postgraduate program, at Thu Dau Mot University. The results showed that the participants could employ skimming and scanning. However, they seemed to be passive in evaluating sources and did not pay much attention to note-taking skills, which are considered really necessary in writing literature review for a research paper or a thesis. The findings suggest that critical reading skills should be taught at the beginning of the course in order to help M.A. students develop their critical reading skills and support them in doing their mini research projects.